The Impact of Extensive Reading on Vocabulary Acquisition in Junior High School - Fitrah, Ayunda; Retnaningdyah, Pratiwi; Mustofa, Ali (Institut Agama Islam Negeri Palopo, 2025)
This essay explores the impact of Extensive Reading (ER) on vocabulary acquisition among junior high school students, highlighting its potential as an effective and engaging language-learning strategy. ER emphasizes reading a variety of texts chosen based on personal interests, creating a natural and immersive environment for students to encounter new words in meaningful contexts. Unlike traditional vocabulary instruction, ER fosters incidental learning, encouraging students to develop language skills through enjoyable and authentic reading experiences. To assess its effectiveness, this study analyzed the pre- and post-ER vocabulary scores of 21 junior high school students. The results revealed a statistically significant improvement in their vocabulary knowledge, underscoring the effectiveness of ER in promoting language growth. These findings not only validate the role of ER in enhancing vocabulary acquisition but also shed light on its broader potential for improving overall language proficiency. By incorporating ER into language curricula, educators can offer a more holistic and student-centered approach to language learning. This research highlights the importance of integrating ER into educational frameworks to cultivate lifelong reading habits while simultaneously boosting linguistic competence. As such, this study provides valuable insights for educators, policymakers, and researchers aiming to enhance language instruction for junior high school learners.